2005
DOI: 10.1007/s00438-005-0055-y
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of 5′- and 3′-untranslated regions of plastid mRNAs to the expression of Chlamydomonas reinhardtii chloroplast genes

Abstract: Expression of chloroplast genes is primarily regulated posttranscriptionally, and a number of RNA elements, found in either the 5'- or 3'-untranslated regions (UTRs) of plastid mRNAs, that impact gene expression have been identified. Complex regulatory and feedback mechanisms influence both translation and protein accumulation, making assignment of roles for specific RNA elements difficult. To identify specific contributions made by various UTRs on translation of plastid mRNAs, we used a heterologous gfp repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
86
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(92 citation statements)
references
References 56 publications
4
86
0
2
Order By: Relevance
“…Franklin et al [44] showed an 80-fold increase in expression levels of GFP (green fluorescent protein) in C. reinhardtii chloroplasts when a synthetic GFP gene with increased AT content (66% AT content in synthetic GFP in comparison to native GFP with 60% AT content) was used. Furthermore, as the 5'-UTR region of chloroplast mRNAs has a profound effect on the translational efficiency of C. reinhardtii chloroplast genes [45,46], the use of different 5'-UTRs of chloroplast genes such as the 5'-UTR of the plastid psbA gene (D1 protein of photosystem II), combined with a strong promoter, could serve as another approach to enhance hGAD65 expression in C. reinhardtii cells. One additional strategy to improve hGAD65 expression may be the use of different host strains of C. reinhardtii.…”
Section: Discussionmentioning
confidence: 99%
“…Franklin et al [44] showed an 80-fold increase in expression levels of GFP (green fluorescent protein) in C. reinhardtii chloroplasts when a synthetic GFP gene with increased AT content (66% AT content in synthetic GFP in comparison to native GFP with 60% AT content) was used. Furthermore, as the 5'-UTR region of chloroplast mRNAs has a profound effect on the translational efficiency of C. reinhardtii chloroplast genes [45,46], the use of different 5'-UTRs of chloroplast genes such as the 5'-UTR of the plastid psbA gene (D1 protein of photosystem II), combined with a strong promoter, could serve as another approach to enhance hGAD65 expression in C. reinhardtii cells. One additional strategy to improve hGAD65 expression may be the use of different host strains of C. reinhardtii.…”
Section: Discussionmentioning
confidence: 99%
“…Microalgae have recently attracted attention as potential lowcost platform for the production of a broad range of commercial products including biofuels, nutraceuticals, therapeutics, industrial chemicals and animal feeds [1][2][3][4][5][6][7][8][9][10][11]; and genome engineering will enable and enhance algae-produced bio-products [1,5,6,[12][13][14][15][16][17][18][19]. However, while much has been written about the potential of transgenic microalgae, little of that potential has yet to be commercialized.…”
Section: Introductionmentioning
confidence: 99%
“…16 The promoter regions are responsible for initiating transcription, while 5' UTRs function to regulate both mRNA stability as well as translation. 19 The 3' UTRs appear to influence mRNA processing and stability, [20][21][22][23] but may also interact with 5' UTRs to influence translation. 19,24 In general, the regulation of chloroplast gene expression is primarily controlled at the level of translation.…”
mentioning
confidence: 99%
“…19 The 3' UTRs appear to influence mRNA processing and stability, [20][21][22][23] but may also interact with 5' UTRs to influence translation. 19,24 In general, the regulation of chloroplast gene expression is primarily controlled at the level of translation. [25][26][27] Three of the human therapeutic proteins; domain 14 of fibronectin (14FN3), VEGF and HMGB1 expressed well in each of the three vectors (table 1).…”
mentioning
confidence: 99%